Impacts of Experimental Flooding on Microbial Communities and Methane Fluxes in an Urban Meadow, Baton Rouge, Louisiana - King, Gary M.; Henry, Katherine (Frontiers in Ecology and Evolution, 2019)
The impacts of flooding on microbial communities and their activities in rice paddy soils have been well documented. However, little is known about the responses of urban soil microbial communities. To assess resistance and resilience to short-term flooding, surface soil samples and intact soil cores were collected from an urban meadow bisected by Dawson Creek in Baton Rouge, LA. All samples were collected subsequent to the unprecedented flood of south central Louisiana during August, 2016, which ensued after deposition of some 27 trillion liters of water. During the flood, an area (lower meadow) adjacent to Dawson Creek was inundated for an unknown period lasting at least several days, while an elevated area (upper meadow) was not flooded. Microbial community composition and diversity at each site were assessed for soils collected from core sections at intervals over a 10-cm depth before and after 3 days of experimental flooding ex situ. Cores from both lower and upper meadow sites were also used to assess methane fluxes before and after the experimental flooding. The results indicated that methane fluxes differed between lower and upper meadow sites, and that they were not resistant to flooding. Lower meadow cores emitted methane prior to flooding and rates increased substantially post-flooding; upper meadow cores consumed methane to levels below ambient atmospheric concentrations prior to flooding, but emitted methane post-flooding. In contrast both lower and upper meadow microbial communities were resistant to short-term flooding, with no significant changes observed at either site, or at any depth interval from the surface to 10 cm. However, lower and upper meadow soil communities differed significantly, with distinct distributions of Acidobacteria, Nitrospirae, and Thaumarchaeota among others. Based on responses of soil cores to experimental flooding, the differences between sites in microbial communities do not appear to be residual effects of the August, 2016 flood, but rather appear to arise from physical, chemical, and biological variables that change along a 4-m elevation gradient. Collectively, the results suggest that the composition and diversity for some urban soils might be insensitive to short-term flooding, but that important biogeochemical processes, e.g., methane fluxes, might respond rapidly.